The in vitro and in vivo investigation of biological activities and phenolic analysis of Helichrysum plicatum subsp. plicatum - ŞENKARDEŞ, İSMAİL; ÇAM, MUHAMMET EMİN; TAŞKIN, TURGUT (UNIV SAO PAULO, CONJUNTO QUIMICAS, 2020)
In Turkey, Helichrysum genus is represented by 26 taxa belonging to 20 species in Turkish flora of which 14 ones arc endemic to Turkey. The aerial parts of Helichrysum plicatum subsp. plicatum are used kidney stones, kidney and stomach ailments. The extraction procedures and solvents are important step in processing of bioactive constituents from the plant materials. Therefore, the aim of this study was to evaluate in vitro antioxidant, antimicrobial, anti-urease, anticholinesterase and in vivo anti-inflammatory activities of Helichrysum plicatum subsp. plicatum different extracts. In addition, the phenolic characterization of the Soxhlet and maceration methanol extracts which showed significant antioxidant, anti-urease, antimicrobial, anti-inflammatmy and anticholinesterase activities were performed by HPLC-DAD and LC-MS/MS. In the present study, the Soxhlet methanol extract exhibited strong antioxidant, antimicrobial and anticholinestemse activities than other extracts. The maceration methanol extract showed the strongest anti-urease activity. The Soxhlet methanol and maceration methanol extracts showed in vivo anti-inflammatory activities very close to each other. As a result of this study, chlorogenic acid, dicaffeoylquinic acid, luteolin, luteolin-7-O-glucoside, naringenin-O-hexoside and isoquercitrin compounds were analysed in plant. Therefore, it is thought that methanol extracts can be used as a natural source in the future for food and pharmaceutical industries.
Keywords: Helichrysum plicatum subsp; plicatum; Anti-inflammatory; Anti-urease; Anticholinesterase; HPLC-DAD-MS; ANTIOXIDANT; FLAVONOIDS; EXTRACT